2018
DOI: 10.1016/j.celrep.2018.02.101
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Structural Modules in a Cooperative RNA Folding Transition

Abstract: SUMMARY Large-scale, cooperative rearrangements underlie the functions of RNA in RNA-protein machines and gene regulation. To understand how such rearrangements are orchestrated, we used high-throughput chemical footprinting to dissect a seemingly concerted rearrangement in P5abc RNA, a paradigm of RNA folding studies. With mutations that systematically disrupt or restore putative structural elements, we found that this transition reflects local folding of structural modules, with modest and incremental cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Recent advances including high-throughput chemical footprinting combined with next-generation sequencing enabled to define remarkably detailed structural features of RNA in association with their biological role. Gracia and others provided a substantial body of evidence for incremental and concerted cooperativity between RNA structural motifs leading to folding of preferential RNA secondary and tertiary structures [ 66 , 67 ]. This cooperativity considers the formation of short-lived intermediates of RNA structure of less preferred thermodynamic stability which affect the kinetics of folding [ 67 ].…”
Section: Rna Structural Arrangementmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances including high-throughput chemical footprinting combined with next-generation sequencing enabled to define remarkably detailed structural features of RNA in association with their biological role. Gracia and others provided a substantial body of evidence for incremental and concerted cooperativity between RNA structural motifs leading to folding of preferential RNA secondary and tertiary structures [ 66 , 67 ]. This cooperativity considers the formation of short-lived intermediates of RNA structure of less preferred thermodynamic stability which affect the kinetics of folding [ 67 ].…”
Section: Rna Structural Arrangementmentioning
confidence: 99%
“…Gracia and others provided a substantial body of evidence for incremental and concerted cooperativity between RNA structural motifs leading to folding of preferential RNA secondary and tertiary structures [ 66 , 67 ]. This cooperativity considers the formation of short-lived intermediates of RNA structure of less preferred thermodynamic stability which affect the kinetics of folding [ 67 ]. Xue and others utilized 15 N relaxation dispersion nuclear magnetic resonance (NMR) combined with chemical probing to capture such intermediates of p5abc subdomain of the Tetrahymena group I intron ribozyme [ 68 ].…”
Section: Rna Structural Arrangementmentioning
confidence: 99%
“…Indeed, recent NMR chemical shift exchange experiments have suggested that P5abc occupies a series of local and rare states that are favorable for tertiary structure formation, essentially breaking down a large-scale conformational process into smaller steps that can occur independently and with only modest kinetic and thermo-dynamic barriers (Xue et al 2016). This model is supported by recent work that identified folding modules within P5abc that each contribute modestly to an overall cooperativity of ∼4 kcal/mol (Gracia et al 2018). Thus, structural modules within a complex RNA "experiment with" different subconformational states, which smooths the energy landscape and speeds folding transitions.…”
Section: A Rugged Landscape Model For Rna Folding?mentioning
confidence: 84%
“…Because RNA typically follows a hierarchical folding pathway (Tinoco and Bustamante 1999;Zhang et al 2017;Gracia et al 2018;Šponer et al 2018), prediction of RNA secondary structure followed by RNA tertiary structure is often a successful strategy. The pattern of Watson-Crick pairing provides significant constraints that reduce the complexity of tertiary structure prediction.…”
Section: Hierarchical Rna Foldingmentioning
confidence: 99%